2017
DOI: 10.1007/s10853-017-1078-6
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional ferrimagnetic glass–ceramic for the treatment of bone tumor and associated complications

Abstract: Silver-containing ferrimagnetic glass-ceramic (Ag-SC45) was synthesized by means of melt and quenching technique. Samples were subjected to morphological, compositional, structural analyses, ability to generate heat, magnetic measurements at high and low magnetic field and antibacterial test using S. aureus strain. The influence of silver introduction and the effect of annealing process were investigated. Morphological, compositional and structural analyses evidenced the formation of metallic silver particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The power dissipated by magnetic scaffolds is a function of the frequency and intensity of the applied magnetic field, which can be tuned, tailored and remotely controlled [31], [34], [35], [38]. Moreover, power losses are strictly related to magnetic phase in bone scaffold, to particle radius and blocking temperature of the sample [19], [23], [35]. On the other hand, dissipation depends also on the magnetic susceptibility of the sample (scaffold [32], [34]).…”
Section: Power Dissipation Of Magnetic Biomaterials In Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The power dissipated by magnetic scaffolds is a function of the frequency and intensity of the applied magnetic field, which can be tuned, tailored and remotely controlled [31], [34], [35], [38]. Moreover, power losses are strictly related to magnetic phase in bone scaffold, to particle radius and blocking temperature of the sample [19], [23], [35]. On the other hand, dissipation depends also on the magnetic susceptibility of the sample (scaffold [32], [34]).…”
Section: Power Dissipation Of Magnetic Biomaterials In Tissuesmentioning
confidence: 99%
“…A temperature raise of 13°C was obtained after 50 min, leading to a decrease in fracture rate [15]. After that, different kinds of ferro- [15], [16] and ferrimagnetic glass [16], [17] ceramics have been synthetized and characterized to ensure the use of these biomaterials for HT purposes [16]- [19]. Further interesting and innovative scaffolds biomaterials, able to perform in situ HT of bone tumor, are based on superparamagnetic iron oxide nanoparticles (SPIONs) [20].…”
mentioning
confidence: 99%
“…Biocompatible magnetic glasses have recently attracted the attention of several research groups for possible use in the advanced treatment of bone cancer as a complementary approach to chemotherapy, which is known to carry many side effects to patients. Fe 3 O 4 -containing melt-derived glass-ceramics were extensively investigated in a series of studies by Verné and coworkers and were found highly promising for the treatment of osseous tumors by hyperthermia [ 12 , 13 , 14 ]. Interestingly, a pro-osteogenic activity was observed in an acrylic-based composite bone cement containing 10% of ferrimagnetic glass-ceramic, with a synergistic effect between bioactivity and cell mineralization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive glasses are considered as coating materials for different substrates to provide surface bioactivity, and this aspect is covered in papers describing different coating methods involving bioactive glasses on a variety of substrates [30][31][32][33][34]. Other publications deal with innovative technologies to produce bioactive phosphate glass fibers [35], 3D scaffolds based on additive manufacturing methods [36], multifunctional ferrimagnetic [37] and bioinspired bioactive glass-ceramics [38] as well as novel polyphenol-functionalized bioactive glasses [39].…”
Section: ó Springer Science+businessmentioning
confidence: 99%